Classroom Design as a Way of Motivating Students for Artistic Activities - Batič, Janja; Lebar Kac, Petra (Selected Contemporary Research on Special Needs, Giftedness, and Talent in Slovenia, 2025)
In this chapter, we present the results of a case study that we conducted to discover how the equipment and space of a design in a universal classroom can encourage students’ spontaneous artistic expression. The study included fifth-grade students and their generalist teacher. In the 2022–2023 school year, pupils were offered an art station that included various art materials and art challenges. We aimed to determine how students would utilize the space for artistic expression, their approach to selecting art materials, and their attitude toward art activities outside of art classes. Data were collected by analysing the teacher’s observation diary, photographs of the art works, and student surveys. The results showed that the art station was very well received by the students and that the most popular material for modelling was clay. Spending free time with friends was also a very important aspect of the art station.